1998
DOI: 10.1111/j.1524-4725.1998.tb04167.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologistsʼ Attitudes toward Independent Nonphysician Electrolysis Practice

Abstract: Dermatologists' attitudes toward INE generally appear to be positively related to perceived licensure requirements for INE, but these positive attitudes do not extend to independent laser use by nonphysician electrologists for hair removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A recent survey indicated that there was very little support (5.7%) by dermatologists for laser hair removal by independent nonphysician electrologists. 1 In order to further understand this issue, an additional survey of both dermatologists and electrologists was conducted.…”
mentioning
confidence: 99%
“…A recent survey indicated that there was very little support (5.7%) by dermatologists for laser hair removal by independent nonphysician electrologists. 1 In order to further understand this issue, an additional survey of both dermatologists and electrologists was conducted.…”
mentioning
confidence: 99%